Pengaruh Persepsi Belajar Bahasa Inggris dan Kesenangan Berbahasa Asing terhadap Kesejahteraan Siswa SMP Negeri 3 Satap Sejangkung - Desinta, Afro' (Inovasi: Jurnal Diklat Keagamaan, 2023)
This study aims to examine the influence of perception and enjoyment of learning a foreign language on the well-being of learning English. This study uses a quantitative approach. The respondents were class VII students (n = 47). The research location is at State Junior High School 3 Satap sejangkung, Sambas, Indonesia. The data collection technique uses a questionnaire. Data collection was carried out in September 2023. The perception measurement instrument was adopted and modified from Dhian Marita Sari and Muslem et al., enjoyment measurement from Dewaele & MacIntyre, well-being assessment from Lo & Lin and Zhu. Data analysis uses normality, linearity, correlation, and regression tests. The results show the influence of the perception of learning English (X1) on the welfare of learning English (Y), with a value (sig.) of 0.000 < 0.05. Perception is strongly correlated with wellbeing (Y) and grades (r = 0.633). There is no influence of the enjoyment variable on English Learning Wellbeing (Y), value (sig.) 0.007 ˂ 0.05. However, it is strongly related (r = 0.709).